2016
DOI: 10.1002/rcm.7699
|View full text |Cite
|
Sign up to set email alerts
|

Competing fragmentation processes of β‐substituted propanoate ions upon collision‐induced dissociation

Abstract: The feasibility of more than one mechanism was established for the fragmentation of β-substituted propanoates. The contribution of each mechanistic pathway to the formation of the substituent anion was influenced by structural variations and conformational constraints, but mostly depended on the nature of the substituent. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In the hydroxy anion of 16c , the double bond between N(a) and N(b) is appropriately positioned for the release of dinitrogen upon the formation of a carbonyl at C(e) (Scheme D). This process is analogous to Grob fragmentation and the favorable decarboxylative elimination found in β‐substituted propanoate ions . The minor and major ions, at m / z 190 and 91 respectively, are consistent with subsequent losses of carbon monoxide and ethyl cyanoformate that occur with the formation of a benzyl anion.…”
Section: Resultssupporting
confidence: 56%
“…In the hydroxy anion of 16c , the double bond between N(a) and N(b) is appropriately positioned for the release of dinitrogen upon the formation of a carbonyl at C(e) (Scheme D). This process is analogous to Grob fragmentation and the favorable decarboxylative elimination found in β‐substituted propanoate ions . The minor and major ions, at m / z 190 and 91 respectively, are consistent with subsequent losses of carbon monoxide and ethyl cyanoformate that occur with the formation of a benzyl anion.…”
Section: Resultssupporting
confidence: 56%
“…In principle, a third pathway involving carboxyl group abstraction of the α‐proton followed by elimination of cyanide is possible. Although a reasonable barrier for the α‐proton abstraction was indicated by previous computations (180–200 kJ mol −1 ), 39 a possible complementary ion (CH 2 =C(NH 2 )CO 2 − , m / z 86) was not detected…”
Section: Resultsmentioning
confidence: 69%
“…In addition to the sequential reactions described above, the three-bond separation of the carboxyl and nitrile groups in β-cyanoalanate (7a) indicated that cyanide (7c) formation by decarboxylative elimination 39,40 was also possible. The transition structure TS 7a-7c located in the computations showed a favorable antiperiplanar alignment of partially cleaved C α -CO 2 À and C β -CN bonds (Figure 5B); however, decarboxylative elimination required a slightly larger energy input than the loss of ammonia (Figure 5A).…”
Section: β-Cyanoalanate (7a)mentioning
confidence: 96%
“…The cyanoacetic acid ester synthesis 46 allowed the synthesis of β 2 -and β 2,2 -amino acids, 47 including alicyclic and heterocyclic β 2,2 -amino acids. 48,49 The application of this methodology to sugars allowed to convert sugar ditriflate 9β into compound 35 (Scheme 7), the first reported polyhydroxylated cycloalkane β 2,2 -amino acid derivative.…”
Section: Papermentioning
confidence: 99%